SISTEM PAKAR PENYAKIT PERNAPASAN PADA ANAK DI UNIT PELAKSANA TEKNIS DINAS (UPTD) PUSKESMAS KANDANG KOTA BENGKULU - Maryaningsih, Maryaningsih; Trianggana, Dimas Aulia (Jurnal Media Infotama, 2011)
This paper describes the making of the application of Expert System Respiratory Disease In Children In Technical Implementation Unit (UPTD) Cage PHC Bengkulu city, using the programming language Visual Basic 6.0 Micrososft. This expert system can identify user issues surrounding the problems of child respiratory illnesses. Its use is similar to the consultation. Used to derive conclusions tracking with forward chaining method (forward tracking). Conclusions derived from the answers to the various questions posed to the user. In addition users can also obtain solutions as well as tips about child diseases, child health care tips. This user know when the user operates the system. By using an expert system diagnoses the child's illness, the user is expected to address the issue of childhood diseases themselves, without waiting for an expert or a real doctor to help resolve the problem.